Optimizing the Yield Product by Changing the Reactor Type for CO2 Hydrogenation in Methanol Synthesis with Process Simulation Software - Zahra, Annisa Diva Karmelia; Muafi, Muhammad Yusuf Zachraey; Rabbani, Nadira Shifa; Ramadani, Muhammad Nuzul (Journal of Chemical Engineering Research Progress, 2025)
Hydrogenation is chosen as a process to reduce CO2 in the air, based on its thermodynamic stability. One of the important things to increase the yield product is by using reactor. This study aims to compare two types of reactor, i.e. equilibrium reactor and conversion reactor. In this study, we made two types of processes as the representative for each type of reactor, by using the reaction and kinetic data from reference. As the result, we investigate the yield product result and the energy used. The number of energy used (in kW) in line to total yield product. For the equilibrium reactor, the yield product and energy used in kilowatt are lesser than the conversion reactor, and for conversion reactor is vice versa. Two of the results state that the higher total amount of energy used the higher total yield product. For the future study, this study could be one of the reference, or could be one of the future consideration for choosing exact reactor based on their needs. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).